Geranyl acetate esterase (GAE) inhibitory activity of Neolamarckia cadamba fruit extract - Gupta, Ashish Kumar; Ganjewala, Deepak (Acta Biologica Szegediensis, 2015)
Neolamarckia cadamba commonly known as the kadamb tree-is well known in Ayurveda and other traditional literature in India for it’s plenty of medicinal properties. Here we report the unique property of the methanol extract of its fruit and a compound isolated from it to inhibit the geranyl acetate esterase (GAE) of lemongrass. The GAE inhibitory activities of the methanol extract and the compound were determined by three procedures, spectrophotometric para-nitrophenyl acetate (p-NPA) assay, polyacrylamide gel electrophoresis (PAGE) and gas chromatography (GC). The results of p-NPA assay revealed that the fruit extract and its compound (10 mg/ml) caused significant inhibition (45%) of GAE activity as compared to the control. PAGE analysis revealed complete inhibition of one of the major isoenzyme of GAE (isoenzyme-II) by both the fruit extract and its isolated constituent. Gas chromatographic analysis showed the fruit extract and its compound caused drastic inhibition of GAE isoenzyme-II by 36 and 46%, respectively. The presence of –C=O and –OH groups in the compound as revealed by FTIR analysis indicated that it belongs to flavonoids. To the best of our knowledge this is the first report on GAE inhibitory activity of N. cadamba fruit methanol extract and its isolated constituent which could be implicated in the future to decipher the catalytic mechanism of GAE. The purification and detailed characterization of the isolated compound is in progress.